Outcomes of Transradial Approach in Terms of Procedural Failure, in Patients Undergoing Percutaneous Coronary Intervention - Iftikhar Ahmed, Iram Jehan Balouch, Syed Ahsan Raza, Lajpat Rai, Faraz Farooq Memon, Altaf Hussain, Atif Ahmed Khan, Ashok Kumar, Rajesh Kumar, Jawaid Akbar Sial (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the outcomes of transradial approach in terms of procedural failure in patients undergoing percutaneous coronary intervention. Methods: We have enrolled a total of 276 patients who consented for percutaneous coronary intervention through trans-radial approach at National Institute of Cardiovascular diseases, Karachi. Baseline and clinical data were collected in a structured questionnaire. Patients were assessed at the end of completion of PCI for the achievement of TIMI grade 3 flow by angiography under the supervision of experienced consultant having >5 years’ experience of intervention. All the data entered and analysed using SPSS version 22.0. Results: Overall mean age of study subjects was 44.86±12.22 years, with range of 52 (18–70) years and among them 194 (70.28%) were males and 82 (29.71%) were females. The overall mean fluoro time was 10.95±4.83 minutes, with range of 22.1 (3.4–25.5) minutes. Our study’s findings have shown no significant association of procedure failure was found with respect to gender, age, CRF, smoking, and obesity, p value <0.05. Significant association of procedure failure was observed in patients with hypertension, diabetes mellitus, family history of ischemic heart disease, hyperlipidemia and fluoro time >10 minutes. Conclusion: Transradial approach becomes the primary choice of vascular access for PCI. The transradial approach eliminates access site complications after PCI. Thus, patients discharge from hospital within 48 hours post-procedure and can mobilize within few hours post-procedure. Keywords: Percutaneous Coronary Intervention, Trans-radial approach, Access outcome, Ischemic heart disease, Pakistan